ORGANIZATION OF STUDENTS' LEARNING ACTIVITIES IN E-LEARNING ENVIRONMENT - Dmitry N. Kryukov; Inna L. Vasilyeva (Moscow Polytechnic University, 2016)
The Federal State Education Standards pay special attention to the organization of students' work with use of active and interactive forms and the methods of training aimed at formation and development of students' professional competences. Changes in the education legislation create additional possibilities of application of the new technologies in the process of training of future specialists. The South-Ural Professional Institute sets a goal to arrange e-education environment based on new the approaches and technologies. The authors focus their attention on electronic modular courses of disciplines.